Interfacial defect passivation by novel phosphonium salts yields 22% efficiency perovskite solar cells: Experimental and theoretical evidence. Issue 1 (21st December 2021) - He, Dongmei; Zhou, Tingwei; Liu, Baibai; Bai, Le; Wang, Wenqi; Yuan, Hongkuan; Xu, Cunyun; Song, Qunliang; Lee, Donghwa; Zang, Zhigang; Ding, Liming; Chen, Jiangzhao
Abstract: We modified perovskite/Spiro‐OMeTAD interface by using two novel phosphonium salts containing PF6 − counter anion (i.e., ClTPPPF6 and BrTPPPF6 ). The cation and anion in phosphonium salts possess not only ionic bonds but also coordination bonds with perovskites. The anion and cation vacancies at the surface and GBs of perovskite films can be filled by phosphonium cations and PF6 − anions, respectively, resulting in reduced defect density and prolonged carrier lifetimes. The stronger chemical interaction and accordingly better defect passivation were certified for BrTPPPF6 than ClTPPPF6 . As a result, the devices modified by ClTPPPF6 and BrTPPPF6 deliver a PCE of 21.73% and 22.15%, respectively, which far exceed 20.6% of the control device. The unsealed BrTPPPF6 modified device maintains 98.2% of its initial efficiency value after thermal aging of 1320 h whereas merely 84.7% for the control device. 96.4% of its original efficiency was retained for BrTPPPF6 ‐modified device after ambient exposure of 2016 h. Abstract : The two novel phosphonium salts are for the first time developed to modify the perovskite/Spiro‐OMeTAD interface. The device with BrTPPPF6 delivers a promising efficiency of 22.15% along with much improved stability.